Moore’s Unyielding Hand: A Robust Defence of Common Sense against Radical Skepticism (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
This paper offers a robust defense of G.E. Moore’s common-sense response to radical skepticism. Against the skeptic’s claim that we cannot know anything about the external world, Moore famously argued that his certain knowledge of common-sense propositions (e.g., “Here is one hand”) serves as a proof that an external world exists. Critics dismiss this as a facile begging of the question, arguing that Moore simply assumes what the skeptic denies. This paper contends that this charge of circularity, while logically valid, misunderstands the dialectical force of Moore’s argument. Rather than attempting to convince the skeptic on their own impossible terms, Moore’s proof performs a foundationalist function. It exposes that the skeptic’s premises are less certain than the common-sense truths they purport to undermine. By holding up his hand, Moore shifts the burden of proof, forcing the skeptic to explain why we should deny our most basic, action-guiding convictions in favor of abstract, hyperbolic doubt. The paper concludes that while Moore’s argument may not be a logical refutation, it is a pragmatically necessary and epistemically legitimate vindication of everyday knowledge. It establishes that common-sense certainty provides a more stable and reasonable starting point for epistemology than the skeptical hypothesis.